ANALISIS PENGARUH WOM, PENGALAMAN BELANJA ONLINE, PERSEPSI KEMUDAHAN DAN PERSEPSI RISIKO TERHADAP MINAT BELANJA ONLINE MELALUI SIKAP BELANJA ONLINE (STUDI PADA ONLINE STORE ELZATTA HIJAB) - Ulumiyah, Lailis; Soesanto, Harry; Sugiono, Sugiono (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2016)
This research is aimed to examine the influence of WOM, online shopping experience, perceived ease, and risk perception of interest in online shopping through online shopping attitude.Sample was men and women that is've shopped at Elzatta Hijab online through the website, a number of 135 respondents. Structural Equation Modeling (SEM) was run by AMOS software was used to analyze the data, analysis showed that WOM online shopping experience, perception and perception of risk through a convenient online shopping attitude positive influence on interest in shopping online.Empirical finding to indicate that WOM positive effect on perceived ease, WOM positive effect on the perception of risk, online shopping experience a positive effect on the perception of convenience, online shopping experience a positive influence on risk perception, perceived ease of positive influence on attitude online shopping, perception of risk has positive effect attitude towards online shopping and online shopping attitude positive influence on interest in shopping online.